Persaksian Perempuan Dalam Surat Al-Bqarah Ayat 282 - Hendri, Yuldi (Musawa Jurnal Studi Gender dan Islam, 2009)
Along with the development of human awareness on gender injustice, the provision of woman witness in lsiamic law needs rethinking. Under the mainstream Islamic law a woman cannot give her witness except in any case moreover her witness is percentaged a half of man witness. Of course, in the outset such provision seems to be gender bias, because the Islamic law treats woman as incapable person. The most moslem scholars comprehended the argumentation texts textually without observing the socio-cultural context of Islamic message and Arabian culture. Nevertheless, the meaning of witness have to be understood as tool of witness proof. Significance of witness is not sex, but the justice and personality integrity witness, and connection of the witness with the fact that she/he sees with the result that the witness is really competent with that problem. If the witness is understood as proof of reality, inequality gender will be overcome. Finally, If we comprehend the religion contextually and progressively So there is no inequality gender will happen. Because Islam is progressive and peace religion and giving equality to everybody,